An appraisal of vessel-source pollution for Malaysian legal framework / Nur Irinah Mohamad Sirat, Syatirah Abu Bakar and Mohd Zulhelmey Abdullah you - Mohamad Sirat, Nur Irinah; Abu Bakar, Syatirah; Abdullah, Mohd Zulhelmey (Research Management Institute (RMI), 2012)
Vessel-source pollution is one of the major sources of marine pollution that harm the coastal marine environment in Malaysia. It contributes quite significantly towards the ecological disturbances of the marine environment as the western coastal area of Malaysia is extremely sensitive to oil spill hazards when most of the area is covered by mangrove forests. The vulnerability of the coastal area was exposed by the recent incident of oil spill washed up onto a 600m coastal stretch located at the Tanjung Piai National Park, Johor which was believed to have occurred when vessels passing by were conducting illegal oil dumping or oil transferring activities (The Star, 2012). The spill has caused the birds and mangrove threes to be covered in oil sludge and it was feared that it would further endanger the species of birds, shellfish and fish, as the oil which has covered mangrove tree roots can cause the plants to wither in two months. (Ahmad Fairuz Othman and Sim Bak Heng, 2012). As Malaysia possesses abundance of coastal natural resources with more than 4670 km of its coastal borders endowed with valuable mangrove swamps, providing breeding and nesting grounds for birds, and egg laying areas for shrimp prawns and turtles (Pourvakhshouri, S.Z, 2004), hazardous consequences of oil spills pose dire threats to these natural environments and its inhabitants. The risks of oil spill come from a number of sources including from tankers passing through the Straits of Malacca which is one of the world's busiest super tanker routes and from a major oil field discovered along the eastern seaboard of Peninsular Malaysia that produces crude oil for exports to other countries. (Pauzi Zakaria M, 2000) Furthermore, existing problems such as oil pollution from bilge pumping and tank cleaning, the dumping of oil and sludge by ocean going vessels as well as oil spills caused by collisions and groundings of ocean-going tankers are among the recurring issues that have yet to be effectively addressed. These matters have invited a thorough examination of the adequacy of the Malaysian legal and regulatory framework in addressing and managing the problem of oil spill particularly vessel source oil pollution in our territorial water. This research thus, will critically analyse the present state of the laws in relation to vessel-source pollution in Malaysia as set against the landscape of the international conventions in order to gauge whether appropriate responses have been made by the Malaysian legislations in view of Malaysian obligations under these conventions and to propose necessary changes accordingly.